Using metaphor and narrative ideas in trauma and family therapy - Witney, Mike N. (HTS teologiese studies, 2012)
Everyday people living in South Africa experience trauma, either first hand through accidents, crime, violence and abuse or through being witnesses to the traumatic event. This results in people in South Africa suffering from anxiety, depression, post-traumatic stress disorder (PTSD) and other severe mental health issues. One only has to read a newspaper, watch or listen to the news to get a glimpse of the landscape of trauma in our country. In this article I looked at using narrative ideas and metaphor in therapy with trauma and family therapy.